Analysis of the Mourning Period (Ihdad) in the Compilation of Islamic Law Based on Sheikh Arsyad al-Banjari’s View - Zulifikri Zulifikri; Fauziah Lubis (JURNAL ILMIAH MIZANI: Wacana Hukum, Ekonomi, dan Keagamaan, 2023)
This study aimed to determine the comparison of the mourning period (ihdad) according to the opinion of Sheikh Arsyad al-Banjari and the Compilation of Islamic Law (KHI). Ihdad was a period during which a wife after the death of her husband. During this time, a wife has various actions that should not be done. KHI also includes it in one of its articles as a legal basis regulating marriage cases. However, the article's contents are unclear enough to regulate this ihdad case. Sheikh Arsyad al-Banjari, a well-known scholar, discusses this issue in the book an-Nikah, which he specifically wrote discussing marriage. So it is good that his opinion can be used until now and can complete the description of Ihdad itself. This research was library research by examining the book an-Nikah and the Compilation of Islamic Law, accompanied by books, journals, and other related sources. This research concludes that according to the views of Sheikh Arsyad al-Banjari regarding ihdad, this lasts for the iddah period, which is four months and ten days; some actions are prohibited during the ihdad period, namely: wearing the same cloth as the colour of jewellery, gold jewellery, silver either rings or necklaces, fragrances both for the body, cloth and food, kohl, hair oil, and henna. Ihdad for women whose relatives died is for three days. While ihdad, according to KHI, is for wives carried out during their iddah period as a form of grief and preventing slander, ihdad for husbands whose wives die is carried out according to appropriateness.Penelitian ini bertujuan guna mengetahui komparasi masa berkabung (ihdad) menurut pendapat syekh Arsyad al-Banjari dan Kompilasi Hukum Islam (KHI).Ihdad merupakan masa dimana seorang istri sehabis ditinggal mati suaminya.Dimasa ini seorang istri memiliki berbagai  perbuatan yang tidak boleh dilakukan.KHI sebagai landasan hukum yang mengatur perkara pernikahan juga turut memasukkannya dalam salah satu pasalnya.Namun isi daripada pasal tersebut belum cukup jelas dalam mengatur perkara ihdad ini. Syekh Arsyad al-Banjari sosok ulama kenamaan membahas persoalan ini dalam kitab an-Nikah,yang secara khusus beliau tulis membahas pernikahan.Maka baiknya pendapat beliau ini dapat digunakan hinga kini serta dapat melengkapi penjabaran ihdad itu sendiri.Penelitian ini merupakan  kajian pustaka (library research) dengan mengkaji kitab an-Nikah dan Kompilasi Hukum Islam, disertai dengan buku,jurnal serta sumber-sumber terkait lainnya. Kesimpulan dari penelitian ini yaitu menurut  pandangan  syekh Arsyad al-Banjari mengenai ihdad ini berlangsung selama masa iddah yaitu empat bulan sepuluh hari ,terdapat perbuatan yang dilarang dilakukan saat masa ihdad yaitu : memakai kain yang sama dengan warna perhiasan, perhiasan emas,perak baik  cincin ataupun kalung, wewangian baik untuk badan, kain dan makanan,celak, minyak rambut,dan inai.Ihdad bagi perempuan yang kerabatnya meninggal,yaitu selama tiga hari. Sementara ihdad menurut KHI yaitu bagi istri dilaksanakan selama masa iddahnya sebagai bentuk duka cita dan mencegah timbulnya fitnah,ihdad  bagi suami yang ditinggal mati istrinya dilaksanakan menurut kepatutan